Inequality, institutons and growth - Tokman, Marcelo (Estudios de Economía, 2016)
The paper explores the relationship between the distribution of wealth and income, the institutional environment and the growth rate of an economy. A formal model is developed in which the members of society determine, through a political process, the extent of property rights protection provided by its institutions. We show that the level of protection is a function of the decisive agent's property share, and that for both a political process requiring a 'strict consensus' and for one consisting in 'majority voting', improvements in the distribution of property result in more secure property rights. The model also predicts that, since increased property rights protection reduces the adverse effects of socio-political instability on savings and investment, improvements in the distribution of wealth and income also lead to higher growth rates.